Malachite Green Removal by Activated Potassium Hydroxide Clove Leaf Agrowaste Biosorbent: Characterization, Kinetic, Isotherm, and Thermodynamic Studies - Dyan Hatining Ayu Sudarni; Uyiosa Osagie Aigbe; Kingsley Eghonghon Ukhurebor; Robert Birundu Onyancha; Heri Septya Kusuma; Handoko Darmokoesoemo; Otolorin Adelaja Osibote; Vincent Aizebeoje Balogun; Bernadeta Ayu Widyaningrum (Adsorption Science & Technology)
Although several approaches have been explored for the removal of dyes and other toxic materials from water as well as the entire environment, notwithstanding, researchers/scientists are still pursuing novel, low-cost, and eco-friendly biosorbents for the effective removal of such contaminants. Herein, clove leaves (CL) were utilized as a biosorbent for the sequestration of malachite green (MG) from a water-soluble solution. The CL was subsequently activated using potassium hydroxide (KOH) and characterized using the FTIR and FESEM to determine the functional groups on the activated clove leaves (CL-KOH) and the morphology of the adsorbent. The adsorption of MG was observed to be relatively dependent on the dosage of sorbent utilized, initial MG concentration, and sorption process contact time. The adsorption process of MG to CL was ideally described using the Dubinin–Radushkevich and Elovich models with the determination of maximum sorption capacity of approximately 131.6 mg·g-1. Furthermore, the thermodynamic parameters calculated showed that the adsorption of MG to the adsorbent was exothermic with the process involving physical sorption as well as chemical sorption processes with negligible adsorption energy. In conclusion, the study has revealed that the CL is a cost-effective biosorbent with high adsorption efficiency for the sequestration of MG from a water-soluble solution and can be recycled for further usage.